PERAN HUKUM DALAM MENGATASI PENYALAHGUNAAN DISTRIBUSI BBM BERSUBSIDI - Sulistiono, Dany (CV. Lafadz Jaya, 2025)
The misuse of subsidized fuel distribution remains a critical issue that results in state losses and misdirected subsidies. The main problem in this study is to examine the extent of the law's role in addressing the misuse of subsidized fuel distribution. The aim of this research is to analyze the legal role in overcoming such misuse, identify the factors affecting the effectiveness of law enforcement, and explore the legal challenges involved in the enforcement process. This study uses a descriptive qualitative method with a literature review approach. The results show that although the law plays an important role in regulation and enforcement, its effectiveness is hindered by weak implementation, lack of coordination between institutions, limited law enforcement resources, and low public legal awareness. The conclusion highlights the need to strengthen the legal system, improve the capacity of law enforcement officers, and encourage public participation in monitoring the distribution of subsidized fuel to ensure fairness and accuracy in its allocation.